2022
DOI: 10.3390/jcm11061630
|View full text |Cite
|
Sign up to set email alerts
|

Non-Small-Cell Lung Cancer Patients with Coexistence of High PD-L1 Expression and RET Fusion—Which Path Should We Follow? Case Reports and Literature Review

Abstract: Pembrolizumab is widely used in first-line treatment in patients with advanced non-small-cell lung cancer (NSCLC) with high PD-L1 expression. The activity of pembrolizumab in NSCLC patients with rare molecular alterations is poorly characterised. RET gene rearrangements are identified in 1–2% of lung cancer patients. Here, we present two cases of RET-rearranged NSCLC patients with high PD-L1 expression (>50%), treated with pembrolizumab within routine clinical practice. Pembrolizumab was ineffective in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…In a separate case series, Rodriguez et al. observed that patients with RET -arranged lung cancers and high PD-L1 expression exhibited positive responses to immunotherapy ( 32 ). Furthermore, Baby, S. et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate case series, Rodriguez et al. observed that patients with RET -arranged lung cancers and high PD-L1 expression exhibited positive responses to immunotherapy ( 32 ). Furthermore, Baby, S. et al.…”
Section: Discussionmentioning
confidence: 99%
“…Selpercatinib, similar to other molecular-targeted therapies, had sufficient systemic effects (12,13), including brain metastases (14). In general, first-line treatment for gene mutation-positive lung adenocarcinoma is the corresponding molecular-targeted drug; however, this case suggests that the order of drugs used may be important when aiming for the longest overall survival by sequence therapy (15). In a phase 3 study of selpercatinib for RET-positive lung cancer, the efficacy of molecular-targeted drugs, in addition to the therapeutic effects Pathologic findings from the first diagnostic cell block showed adenocarcinoma in the presence of many lymphocytes (A, B, H&E staining, original magnification × 400).…”
Section: Discussionmentioning
confidence: 99%
“…Lung tumors with RET fusions usually appear in patients without a smoking history. Such tumors tend to have a low tumor mutation burden (TMB) and are poorly infiltrated by immunological cells, which in effect present low expression of PD-L1, and hence weak response to ICIs [ 63 ].…”
Section: Immunotherapy In Tumors With Genetic Changes Of Ret Genementioning
confidence: 99%